SURFACE-CHARGE PROPERTIES AND UO2+2 ADSORPTION OF A SUBSURFACE SMECTITE - Turner G.D.; Zachara J.M.; McKinley J.P.; Smith S.C. (My University, 1996)
Surface charge and UO22+ adsorption were measured on a clay-sized, subsurface mineral isolate whose mineralogy was dominated by a ferrogenous beidellite. Experiments were performed in batch at 25°C with N2(g) atmosphere and sorbent suspensions (9.46 g clay/kg suspension) that had been adjusted in pH between 4 and 9. Surface charge was defined by measurements of adsorbed Na by isotopic exchange and of proton adsorption by potentiometric titration in NaClO4 (I = 0.1, 0.01, 0.001). Extraction of the clay with La(NO3)3 and aqueous-phase analyses were necessary to establish the contributions of Al and Si dissolution to the proton balance and the total adsorbed cation charge (i.e., Naads+ + 3Alads3+). The adsorption of UO22+ (7.5 × 10−6 mol L−1) was determined in Na+ (0.1, 0.01, 0.001 mol L−1) and Ca2+ (0.05 and 0.005 mol L−1) electrolytes. Adsorption of UO22+ showed contributions of ion exchange and edge complexation reactions in Na+ electrolyte, but by only edge complexation reactions in Ca2+ electrolyte. A multiple-site surface-complexation model containing fixed- X− and variable-charge sites (SiOH, AlOH) was fit to adsorbed cation charge data between pH 4 and 10, with the concentrations of AlOH, SiOH, and X− as the adjustable parameters. Surface acidity and ion-pair formation constants for gibbsite and silica were used to describe the ionization and electrolyte binding of the AlOH and SiOH sites. The model provided an excellent description of the surface-charge characteristics of the clay as measured by sodium isotopic exchange and potentiometric titration. A composite model was formulated to predict UO22+ adsorption by incorporating UO22+ aqueous speciation, competitive ion exchange with background electrolyte cations, and UO22+ complexation with AlOH and SiOH sites. UO22+ complexation with AlOH and SiOH was parameterized by UO22+ sorption on α-Al(OH)3(s) and α-SiO2(s), respectively. The composite model overpredicted UO22+ sorption across the entire pH range in both electrolytes. Acceptable predictions could be obtained if the UO22+ affinity for edge AlOH sites were adjusted 2.03 log units below that of gibbsite. Changes in chemical affinity arising from lattice substitutions and edge site morphology are, therefore, concluded to contribute significantly to adsorption, although the potential competitive effects of dissolved Al3+ and H4SiO4 could not be discounted. The adsorption of UO22+ on the subsurface smectite was similar to that of the reference montmorillonite, SWy-1, with the exception that Al dissolution contributed significantly to adsorbed cation charge.